Determinan Ketepatan Pelaporan Keuangan pada Koperasi Serba Usaha di Kabupaten Bangli - Satwika, Ni Nengah Meri Angga; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2021)
This research was conducted to examine the effect of SPI, HR competence, IT management, and profitability on the accuracy of cooperative financial reporting. The research was conducted at the Multipurpose Cooperative in Bangli Regency. The sample in this study was 20 KSU using purposive sampling technique. The respondents of each KSU consist of 4 people, namely the chairman, treasurer, cashier and supervisor of the cooperative. Technique data by distributing questionnaires. Then the data were analyzed using descriptive statistical analysis, classical assumption test, multiple linear regression analysis. Presentation of data was assisted by the SPSS 20 for windows program. The research shows that: SPI, HR competence, IT utilization, and profitability have a positive effect on the accuracy of KSU's financial reporting.